Pengaruh Literasi Digital dan Kemampuan Berpikir Kritis Terhadap Hasil Belajar Siswa Kelas VII pada Mata Pelajaran Informatika di SMPN 3 Kedungwaru - Ramadhani, Nur'Ani; Panggayuh, Vertika; Pamungkas, Bian Dwi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of digital literacy and critical thinking skills, both partially and simultaneously, on the learning outcomes of seventh-grade students at SMP Negeri 3 Kedungwaru. The study used a quantitative approach with an ex post facto type. The study population was 193 students, with a sample of 130 students selected using proportional random sampling techniques. Data were collected through questionnaires and grade documentation, then analyzed using multiple linear regression with the help of SPSS version 25. The results showed that digital literacy had a positive and significant effect on learning outcomes (sig. = 0.000 < 0.05). Critical thinking skills also had a positive and significant effect on learning outcomes (sig. = 0.000 < 0.05). Simultaneously, digital literacy and critical thinking skills had a positive and significant effect on learning outcomes (sig. = 0.000 < 0.05). The coefficient of determination (R²) of 0.893 indicates that both variables contributed 89.3% to learning outcomes, while the remaining 10.7% was influenced by factors outside the study. This finding suggests that improving digital literacy and critical thinking skills play a significant role in improving student learning outcomes.